PREDICTION OF SOLAR CYCLE 24 USING FOURIER SERIES ANALYSIS - Khalid, M.; Sultana, M.; Zaidi, F. (The Nucleus, 2014)
Predicting the behavior of solar activity has become very significant. It is due to its influence on Earth and the surrounding environment. Apt predictions of the amplitude and timing of the next solar cycle will aid in the estimation of the several results of Space Weather. In the past, many prediction procedures have been used and have been successful to various degrees in the field of solar activity forecast. In this study, Solar cycle 24 is forecasted by the Fourier series method. Comparative analysis has been made by auto regressive integrated moving averages method. From sources, January 2008 was the minimum preceding solar cycle 24, the amplitude and shape of solar cycle 24 is approximate on monthly number of sunspots. This forecast framework approximates a mean solar cycle 24, with the maximum appearing during May 2014 (± 8 months), with most sunspot of 98 ± 10. Solar cycle 24 will be ending in June 2020 (± 7 months). The difference between two consecutive peak values of solar cycles (i.e. solar cycle 23 & 24 ) is 165 months[± 6 months].